Generation-Y Singaporeans : negotiating the Singapore identity vis-à-vis the influx of foreigners. - Loh, Desiree Jiawen. (2013)
The topic of foreigners has been much debated about in recent years. Although a necessary contribution to Singapore’s economic success, foreigners has also been perceived as a threat to the Singapore culture/identity. Through conducting twenty in-depth qualitative interviews, this paper examines how Generation-Y Singaporeans construct and negotiate their Singapore identity in the face of foreign influx. From the data collected, two contrasting patterns which respondents negotiate their Singapore identity by emerged. Firstly, respondents strengthen their Singapore identity by drawing upon their communicative memories and enforcing role obligations; secondly, they distance the foreigner through use of cultural identifiers based upon stereotypes. Lastly, a comparison across races concludes various degrees of acceptance towards foreigners. The relevance of traditional literature understanding nationalism in the Singapore context is also challenged. This study suggests the need to re-evaluate current immigrant policies and integration initiatives that are becoming increasing disjunctured from the hearts of local Singaporeans.